An exploratory study on how toilet education in Singapore reproduces inequality with social class assumptions - Tay, Jia Yi (2016)
In Singapore, the toilet educational posters can only be mostly found in neighbourhood malls and not in town malls. In conflict theorists’ perspectives, formal education reproduces inequality. Using this as the theoretical framework, this research paper aims to shed light on the assumptions made about different social classes through the placement of toilet educational posters in Singapore to reveal the reproduction of inequality in toilet education. Email and qualitative interviews are conducted with the shopping malls and the general public to understand the assumptions that they withhold about social classes. Toilet education in Singapore is indeed found to be influenced by these assumptions in the data analysis part. Education appears to keep value consensus in the society but at the same time we are instill with some class assumptions in the course of it, making education to reproduce inequality instead.